Distorsiones cognitivas y su influencia en la conducta social de un paciente con covid – 19 de la ciudadela La Ventura de la ciudad de Babahoyo en el periodo 2020 -2021 - Vargas Yanez, Omar (2021)
The case study to be carried out describes the cognitive distortions that a patient with Covid-19 may present and how they influence social behavior. Because currently Ecuador has a high rate of infected with this disease. Cognitive distortions are the error that one has to process information, that is, many of the people misinterpret the information obtained and social behavior is the behavior that one has towards society. A clinical case was presented where the patient presented the Covid-19 disease in addition to cognitive distortions and problems in social behavior, individual interviews and psychological tests were carried out to help us establish a diagnosis and develop a therapeutic scheme in order to improve the problem. For the treatment, it was chosen to use Cognitive Behavioral Therapy that stands out in modifying said dysfunctional thoughts, automatic thoughts, negative thoughts, irrational ideas and cognitive distortions in order to improve or change the patient's behavior. It should be noted that CBT has provided knowledge and theoretical ideas and effective treatments in anxiety disorders, depression among others, which will help in the problem in question.